Ligand isotope vibrational spectroscopic and DFT studies of Pt(II) and Cu(I) complexes - Medina, Gerardo Juan (Rhodes University, Faculty of Science, Department of Chemistry, 2005)
Ligand-isotope labelling studies were performed on Zeise's salt derivatives with pyridine N-oxide and quinoline N-oxide, their perdeuterated and O-18 isotopomers, Câ‚‚Dâ‚„ and Â¹Â³CO, and the results of the vibrational analyses are reported. The isotopomers are modelled utilizing DFT calculations at the B3LYP level with the 6-31 G** basis set, and a pseudopotential level for the Pt atom. The calculated and observed structure and vibrational spectra correlate well. The crystal structures of [Pt(Câ‚‚2Hâ‚„)(pyO)Clâ‚‚] and [Pt(CO)(quinO)Brâ‚‚] are reported. The frequency for the Î½Pt-O vibration, ambiguously assigned in the literature, is here assigned unequivocally at 400 cmâ »Â¹. Previously observed, but inadequately described phenomena are addressed: the Î½N-O vibration in substituted quinoline N-oxides has been assigned previously at significantly different frequencies, depending on the nature of the substituent. This suggests that there is no specific mid-ir band associated with a high N-O character. A suitable explanation is presented for this phenomenon, showing that in low symmetry systems (eg. quinO) the N-O stretch is dispersed among several modes, whereas in high symmetry systems (eg. pyO) only a few limited modes have a high N-O character. A theoretical study of Cu(I) carbonyl compounds with macrocyclic ligands is presented. Local and global HSAB parameters applied to the donor and Cu atoms are used to explain the observed reactivities and the available spectroscopic data. Extended to [Cu(CO){Hâ‚‚N(CHâ‚‚)[subscript n]NH(CHâ‚‚)[subscript m] NHâ‚‚}] BPhâ‚„ (where n = 2, m = 2, 3 and n =3, m = 3, 4) and their -dâ‚… and Â¹Â³CO isotopomers, subtle differences obtained experimentally for the CO stretching frequency in this series have been reproduced in the DFT calculations at the B3LYP level, using the 6-31 G* and 6-31 G** basis sets. Several properties (ligand pK[subscript a] values, Î½CO frequencies, etc.) correlate with some HSAB descriptors. Vibrational analyses are presented of Cu(I) carbonyl Schiff-base derivatives of N-Benzylidene-N'-[2-(benzyilidene-amino)-ethyl]-ethane-1,2-diamine, {2,2N3(Câ‚†Hâ‚„R)â‚‚}, and their -dâ‚… and Â¹Â³CO isotopomers. The crystal structure of [Cu(CO){2,2N3(Câ‚†Hâ‚…)â‚‚}]BPhâ‚„ is reported. From geometry optimizations and the HSAB descriptors, spectroscopic trends ([n]Cu-N and [nu]CO) are related to calculated global hardness and the Hammett substituent parameters, and are discussed in terms of Ïƒ-donation and Ï€-backbonding of Cu- CO.
Keywords: Ligands; Spectrum analysis; Vibrational spectra; Infrared spectroscopy